Comparative effects of chronic administrations of gabapentin, pregabalin and baclofen on rat memory using object recognition test - Asma Salimzade; Ali Hosseini-Sharifabad; Mohammad Rabbani (Research in Pharmaceutical Sciences, 2017)
Memory impairment is one of the greatest concerns when it comes to long-term CNS-affecting drug administration. Drugs like gabapentin, pregabalin and baclofen are administered in a long-term period in conditions such as epilepsy, neuropathic pain, spasticity associated with spinal cord injury or multiple sclerosis. Despite their wide spread use, few data are available on the effects of these drugs on cognitive functions, such as learning memory. In the present study, the effects of long-term administration of gabapentin, pregabalin and baclofen on memory were investigated in a comparative manner. Male Wistar rats received intraperitoneal (i.p.) injection of gabapentin (30 mg/kg), pregabalin (30 mg/kg), baclofen (3 mg/kg), combination of gabapentin/baclofen (30/3 mg/kg) and combination of pregabalin/baclofen (30/3 mg/kg) once a day for 3 weeks respective to their groups. After the end of treatments, rat memories were assessed using the object-recognition task. The discrimination and recognition indices (RI and DI) in the T2 trials were used as the memory indicating factors. The results showed that daily i.p. administrations of pregabalin but not gabapentin or baclofen significantly decreased DI and RI compared to saline group. In combination groups, either gabapentin or pregabalin impaired discrimination between new and familiar objects. Our findings suggested that pregabalin alone or in combination with baclofen significantly caused cognitive deficits.